RELATIONSHIP BETWEEN BODY MASS INDEX LEVELS AND THE GRADES OF HYPERMESIS GRAVIDARUM IN TORA BELO REGIONAL HOSPITAL, SIGI REGENCY - Qolbi, Zuhrotul; White, I Putu Fery Immanuel; Sumarni; Rupawan, I Kadek (Fakultas Kedokteran Universitas Alkhairaat, 2025)
ABSTRACT Hyperemesis Gravidarum (HG) is a condition of severe nausea and vomiting in pregnant women which has many negative impacts, including economic losses due to treatment costs, the threat of maternal and fetal safety, also adverse pregnancy outcomes such as Chronic Energy Deficiency (CED), the birth of Low Birth Weight (LBW), to stunting. The risk factors for HG are multifactorial, with one modifiable risk factor is Body Mass Index (BMI) levels. Quantitative research with analytic observational design and cross-sectional approach, analyzed using Somers' d test. Data from 63 patients, the majority had an underweight (44.4%). The grades of HG in the sample there are 2 types, namely grade 1 and grade 2, with 93.7% of patients are in grade 2. Somers’ d test showed a significant relationship between BMI levels and the grades of HG with a value of p = 0.049 (p <0.05). The correlation obtained was a negative correlation (r=-0.201). The relationship was also supported by additional data that the most HG patients who has positive ketonuria, abnormal heart rate, and blood pressure, were patients with underweight. Most patients were young adults (88.9%), with multigravida (44.4%) and primipara (36.5%). Most patients had never an abortion (76.2%). There is a significant negative correlation between BMI levels and the grades of HG, namely that the lower the patient's BMI level, the more severe the grades of HG. ABSTRAK Hiperemesis Gravidarum (HG) merupakan kondisi mual dan muntah hebat pada ibu hamil yang memiliki banyak dampak negatif, antara lain kerugian ekonomi akibat biaya pengobatan, ancaman terhadap keselamatan ibu dan janin, serta luaran kehamilan yang tidak diharapkan seperti Kekurangan Energi Kronis (KEK), kelahiran Berat Badan Lahir Rendah (BBLR), hingga stunting. Faktor risiko HG bersifat multifaktorial, dengan salah satu faktor risiko yang dapat dimodifikasi adalah kadar Indeks Massa Tubuh (IMT). Penelitian kuantitatif dengan desain observasional analitik dan pendekatan cross-sectional, dianalisis menggunakan uji Somers' d. Hasil penelitian menunjukkan data dari 63 pasien, mayoritas memiliki berat badan kurang (44,4%). Derajat HG pada sampel ada 2 jenis, yaitu derajat 1 dan derajat 2, dengan 93,7% pasien berada pada derajat 2. Uji Somers' d menunjukkan adanya hubungan yang signifikan antara kadar IMT dengan derajat HG dengan nilai p = 0,049 (p < 0,05). Korelasi yang diperoleh adalah korelasi negatif (r=-0,201). Hubungan tersebut juga didukung oleh data tambahan bahwa pasien HG yang memiliki ketonuria positif, denyut jantung abnormal, dan tekanan darah paling banyak adalah pasien dengan berat badan kurang. Pasien terbanyak adalah dewasa muda (88,9%), multigravida (44,4%) dan primipara (36,5%). Pasien terbanyak tidak pernah melakukan abortus (76,2%). Simpulan: Terdapat korelasi negatif yang signifikan antara kadar IMT dengan derajat HG, yaitu semakin rendah kadar IMT pasien, maka derajat HG semakin berat.